2021
DOI: 10.1002/aenm.202003071
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Electron‐Phonon Interplay and Dynamical Energy‐Dissipation Mechanisms of Hot Carriers in Hybrid Lead Halide Perovskites

Abstract: The discovery of slow hot carrier cooling in hybrid organic–inorganic lead halide perovskites (HOIPs) has provided exciting prospects for efficient solar cells that can overcome the Shockley–Queisser limit. Questions still loom over how electron‐phonon interactions differ from traditional polar semiconductors. Herein, the electron‐phonon coupling (EPC) strength of common perovskite films (MAPbBr3, MAPbI3, CsPbI3, and FAPbBr3) is obtained using transient absorption spectroscopy by analyzing the hot carrier cool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 71 publications
(129 reference statements)
4
44
0
Order By: Relevance
“…𝑑𝑛 ℎ𝑙 𝑑𝑡 population density from 400 to 650 fs, as was previously observed and attributed to the hot-phonon bottleneck effect. [21][22][23][25][26][27]43 The observed timescales of both cooling processes are in excellent agreement with Bretschneider et al 58 However, the fact that a ~450 fs local lattice cooling timescale kl is observed in our experiment where polaron formation precedes (and is therefore ruled out from) the observed dynamics may point toward an alternative interpretation of their results. bonds that strongly couple to the carriers.…”
Section: Fig 2 Representative Pump-push-probe Transients (Left) Push-...supporting
confidence: 91%
See 2 more Smart Citations
“…𝑑𝑛 ℎ𝑙 𝑑𝑡 population density from 400 to 650 fs, as was previously observed and attributed to the hot-phonon bottleneck effect. [21][22][23][25][26][27]43 The observed timescales of both cooling processes are in excellent agreement with Bretschneider et al 58 However, the fact that a ~450 fs local lattice cooling timescale kl is observed in our experiment where polaron formation precedes (and is therefore ruled out from) the observed dynamics may point toward an alternative interpretation of their results. bonds that strongly couple to the carriers.…”
Section: Fig 2 Representative Pump-push-probe Transients (Left) Push-...supporting
confidence: 91%
“…[21][22][23] A growing number of works implicate polarons in this aspect of the hot carrier behavior too, owing to the enhanced spatial extent, strong coupling to phonons and sharing of phonon subpopulations inherent to overlapping polarons. [24][25][26][27] The interpretation of the transient optical signals that convey the aforementioned relaxation processes in MHP-based materials must be taken with care, especially when pumping far above the bandgap and at high fluences. These conditions can favor a myriad of processes that obfuscate the intraband relaxation, including, but by no means limited to: interband transitions between distinct electronic/spin states, [28][29][30] exciton formation/dissociation, 13,[31][32][33] energy/charge migration, [34][35][36] bandgap renormalization, 21,37 refractive index changes, 21,38 Stark shifting, 39,40 and many-body (Auger) processes.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence and an active role of hot phonons is also commonly revealed in the analysis of the time dependence of electronic properties upon nonequilibrium conditions. Given the plethora of ultrafast pump-probe experiments nowadays accessible, the physical properties under investigation can vary in a wide range, from optical probes (transmission [77,84,85,87,150,151], reflectivity [13,89,[110][111][112][152][153][154], absorption [91,[155][156][157][158]) to non-linear optics [86], time-resolved photoelectron spectroscopy [108,132,133,[159][160][161][162], photoluminescence [83,163], time-dependent Raman probes [164], ultrafast diffraction [6,44,109,126,[165][166][167][168][169][170][171].…”
Section: Detecting Hot Phononsmentioning
confidence: 99%
“…However, the thermalization process of some materials can be hindered by the so-called phonon bottleneck [2,3,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] that quenches the energy transfer between electron and lattice degrees of freedom. Such a physical phenomenon is usually encountered in semiconductors and semimetals where the pump-driven particle-hole excitations are restricted to few single points (valleys) in the Brillouin zone.…”
Section: Introductionmentioning
confidence: 99%